Effect of manipulation of scrotal temperature on clinical, seminal and endocrine characteristics in rams - Huanca L., Wilfredo (2015)
The aim of this study was to assess clinical and seminal characteristics and endocrine changes in rams with scrotal insulation. Twelve Merino rams were randomly distributed into a control group (n=4) and a group with scrotal insulation (n=8), that was done with a cotton bag coated with plastic to increase the temperature to 39.0 °C for 48 h. The volume of ejaculate, testicular consistency, scrotal circumference, sperm concentration, mass and individual motility, and sperm abnormalities were recorded for five weeks. Semen collection by electroejaculation was conducted three times per week. The animals were cannulated in the jugular vein and blood samples were taken for 6 hours at 10 minute intervals for testosterone and LH determination by radioimmunoassay. The results showed changes in scrotal circumference (from 30.43±1.1 to 25.00±0.5 cm on week 5); reduction of sperm concentration (week 2); mass motility: 0 (week 2); individual motility: 2.45±3.1 (week 2); and 82.3±29.3% sperm abnormalities at week 3. Testosterone concentration decreased (280±83 pg/ml) and LH concentrations increased (0.96±0.72 ng/ml) at week 2, including higher number of LH pulses. It is concluded that the increase of scrotal temperature causes changes in the clinical, seminal, and in the secretion of testosterone and LH.